Path Analysis and correlation between quantitative traits in cultivated sugar beet germplasms (Beta vulgaris L.), under rhizomania disease conditions in Miandoab - Mousa Arshad; Behzad Ghanbari taghi abad; Hamid Hatami Maleki; Keivan Fotuhi (پژوهشنامه اصلاح گیاهان زراعی)
Extended Abstract Background: Sugar beet (Beta vulgaris L.) is one of the most important root crops and the main source of sugar. It has the greatest ability to be cultivated in the temperate regions of Iran. One of the main centers for cultivating this crop in Iran is West Azerbaijan Province, which accounts for a major share of its production in the country. Rhizomania disease is among the most important factors limiting the growth and reducing the yield of sugar beet. Given that the use of some agricultural methods, such as planting date, irrigation methods, crop rotation, chemical methods, and biological methods, are not very useful in fighting the disease, the use of resistant cultivars is suggested as the best and only way to fight this disease. So far, several studies have been conducted on obtaining disease-resistant cultivars. The first prepared and cultivated hybrid, called Rizor,  was a relatively resistant monogerm diploid hybrid that significantly increased the yield of sugar beet in contaminated fields. Studies on the genetic diversity of this strategic plant help breeders identify genetic resources resistant to rhizomania disease with breeding objectives, including yield and yield components. It is crucial to be aware of the differences and diversity between different genotypes of sugar beet and the associations of these differences with their potential performance in improving the yield of new cultivars. Since there are mutual effects among the variables in multivariate regression, a variable may be significant next to some variables, but not significant next to some other variables. For this reason, it is necessary to select important variables that have a significant effect on yield. In this regard, this research aimed to evaluate domestic and imported modified varieties of sugar beet under the presence of rhizomania disease in the climatic conditions of Miandoab City. Methods: An experiment in the form of a completely randomized block design with four replications was conducted at the Miandoab Agricultural and Natural Resources Research Center in the geographic location of 46° 90' E and 36° 58' N with at an altitude of 1314 m above sea level. The experimental materials included 12 sugar beet genotypes (10 domestic genotypes with one imported resistant genotype and 1 domestic sensitive genotype). In this study, the studied genotypes were exposed to the natural infection of the region. After determining the percentage of cultivars, the level of resistance and sensitivity of each genotype was determined based on the percentage of infection. Before the experiment, land preparation operations included plowing, disking, leveling, and plotting the field in the same way. Phosphorus and potash fertilizers were applied based on the results of the soil decomposition test at the time of land preparation, and nitrogen fertilizer was used as a starter in the form of plant feet. The seed distances between and on the rows were 60 cm and 15 cm, respectively. The size of each plot included three planting lines with a length of 8 m. Agricultural operations, including irrigation, pest and disease control, and cultivator application, were carried out as needed. Root yield traits, pure sugar percentage by the polarimetric method, gross sugar percentage, pure sugar yield, gross sugar yield, extraction percentage, and molasses sugar percentage were measured after harvest.